The Effect of Equatorial Spread F on Relative Orbit Determination of GRACE Using Differenced GPS Observations - Kyoung-Min Roh; Hermann Luehr; Sang-Young Park; Jung-Ho Cho (Journal of Astronomy and Space Sciences, 2009)
In this paper, relative orbit of Low Earth Orbit satellites is determined using only GPS measurements and the effects of Equatorial Spread-F (ESF), that is one of biggest ionospheric irregularities, are investigated. First, relative orbit determiation process is constructed based on doubly differenced GPS observations. In order to see orbit determination performance, relative orbit of two GRACE satellites is estimated for one month in 2004 when no ESF is observed. The root mean square of the achieved baselines compared with that from K-Band Ranger sensor is about 2 ~ 3 mm and average of 95% of ambiguities are resolved. Based on this performance, the relative orbit is estimated for two weeks of two difference years, 2003 when there are lots of ESF occurred, and 2004 when only few ESF occurred. For 2003, the averaged baseline error over two weeks is about 15 mm. That is about 4 times larger than the case of 2004 (3.6 mm). Ionospheric status achieved from K-Band Ranging sensor also shows that more Equatorial Spread-F occurred at 2003 than 2004. Investigation on raw observations and screening process revealed that the ionospheric irregualarities caused by Equatorial Spread-F gave significant effects on GPS signal like signal loss or enhancement ionospheric error, From this study, relative orbit determination using GPS observations should consider the effect of Equatorial Spread-F and adjust orbit determination strategy, especially at the time of solar maximum.